Identifikasi Parasit pada Ikan Kerapu Sunu, Plectropomus leopardus - Sauyai, Kristian; Longdong, Sammy N.J; Kolopita, Magdalena E.F (e-Journal BUDIDAYA PERAIRAN, 2014)
This research aimed to identify, analyze and determine the prevalence rate and dominance index of parasites on grouper (Plectropomus leopardus) landed at Bahu Beach. The number of samples used was 20 fishes measuring 230,68-490,10 g in weight and 24-29 cm in length. Ectoparasites were observer in mucus, fin, and gill while endoparasites were observed in peritoneal cavity and intestine of fish. Parasites invested grouper were Lernaeocera branchialis, Unitubulotestis sardae Acanthochondria cornuta, Mirasidium Schistosomatium douthiti, Argulus sp and  Gnathia maxillaris. All the parasites were found in fish gill and only one species in the mucus. Prevalence rate of parasites was 40%.  Based on parasite species, prevalence rate of  Unitubulotestis sardae was 20%, Acanthochondria cornuta 10%, Gnathia maxillaries 10%, Lernaeocera branchilia 5%, Mirasidium Schistosomatium douthiti 5% and Argulus sp 5%.  Parasites infected grouper dominated by three species namely Unitubulotestis sardae, Acanthochondria cornuta, and Gnathia maxillaris in which all the species were dominant in the gill.   Keywords :  Parasite, Plectropomus leopardus, prevalence rate, dominance index